(3WHbGJ GdabgGA GdTGaYjIs - (3YKeGf Hf UdGM GdOjf CHj GdbGSe YHO GdQMef Hf YKeGf Hf GdUdGM GdTgQRhQj, GdMGaX Jbj GdOjf , CHh YeQh,J (B643 (3g` s ((3GdeOQSI GdUGMHjI GdHgGFjI HeUQ GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg Cced GdMeOd s
(3BNQgG (B:s
(3JfJgi HJQLeI CHj EHQGgje ESeGYjd Hf jMji UGMH GdTGaYi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B612 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B174 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1101s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , HgG NQe s
Keywords: (3GdJGQjNs